DIE KANAÄNITIESE VROU VAN MATTEUS 15: HERVORMER IN EIE REG - Mouton, Elna (Scriptura, 2002)
This worship service was broadcast by Radiosondergrense on the evening of Reformation Sunday, 27 October 2002. I gladly dedicate my interpretation of the Canaanite woman’s story as a humble tribute to Professor HJ Bernard Combrink, respected predecessor in the Faculty of Theology at the University of Stellenbosch where he taught New Testament Studies for 26 years. His own academic journey often dwelled on the gospels of Mark and Matthew - the only gospels to narrate the story of the Syro-Phoenician (Caananite) woman. The "retelling" of her story from within the genre of a worship service, with particular reference to the structure and socio-rhetorical dynamics of Matthew 15:21-28, is presented as a celebration of Reformation Day. Simultaneously it wishes to honour Combrink’s profound respect for both the detail and broad literary and socio-rhetorical contexts of the biblical documents, as well as his concern for their relevance for the liturgy of social life in (South) Africa.